2015
DOI: 10.3748/wjg.v21.i15.4547
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of aquaporin3 expression by lipopolysaccharide via p38/c-Jun N-terminal kinase signalling pathway in HT-29 human colon epithelial cells

Abstract: p38 and JNK may be promising targets for the preservation of AQP3 expression and may be beneficial to the clinical management of diarrhoea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
2
15
1
Order By: Relevance
“…To our knowledge, only one study showed that changes in AQPs expression and water permeability may increase resistance to apoptosis in activated HSCs, although the metabolic impact of glycerol diffusion in activation and quiescence was not analyzed 16 . Importantly, previous studies revealed repression of AQP3 by LPS exposure in human colon epithelial HT-29 cells 17 but induction in murine 3T3-L1 adipocytes 18 , in line with AQP3 upregulation by arachidonic acid or prostaglandin in human retinal pigment epithelial cells, already suggesting a role of JNK 19 . Since in PNPLA3 I148M expressing HSCs the JNK/AP-1 pathway is strongly induced 20 , the subsequent PPARγ downregulation, led us to hypothesize that PPARγ could regulate AQPs expression in HSC in connection to the I148M variant 20 .…”
Section: Introductionsupporting
confidence: 61%
“…To our knowledge, only one study showed that changes in AQPs expression and water permeability may increase resistance to apoptosis in activated HSCs, although the metabolic impact of glycerol diffusion in activation and quiescence was not analyzed 16 . Importantly, previous studies revealed repression of AQP3 by LPS exposure in human colon epithelial HT-29 cells 17 but induction in murine 3T3-L1 adipocytes 18 , in line with AQP3 upregulation by arachidonic acid or prostaglandin in human retinal pigment epithelial cells, already suggesting a role of JNK 19 . Since in PNPLA3 I148M expressing HSCs the JNK/AP-1 pathway is strongly induced 20 , the subsequent PPARγ downregulation, led us to hypothesize that PPARγ could regulate AQPs expression in HSC in connection to the I148M variant 20 .…”
Section: Introductionsupporting
confidence: 61%
“…Lipopolysaccharide, tumor necrosis factor, platelet‐activating factor, IL‐1, and other inflammatory stimuli can induce the activation of P38 in endogenous immune cells such as monocytes, endothelial cells, and neutrophils . P38 activation is closely related to apoptosis and P38 can increase the expression of c‐Myc, phosphorylation of P53 and activation of c‐Jun, to regulate apoptosis . ATF2 is a commonly recognized downstream target of P38 MAPK kinase .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that LPS, mimicking inflammation occurring during obesity, can affect the expression of several aquaglyceroporins. Indeed, LPS down-regulated AQP3 levels in human colon epithelial cells through a p38/JNK signaling pathway [37], but enhanced AQP9 expression in rat brain by an, as yet, uncharacterized signaling pathway [38]. However, it is currently unknown if LPS affects aquaglyceroporin expression in adipocytes.…”
Section: Introductionmentioning
confidence: 99%